O circuito espacial da produção petrolífera no Rio Grande do Norte - Alves, Sandra Priscila (2012)
Our study refers to the state of Rio Grande do Norte against the deployment of oil activity in their territory. In this sense the aim of this work was to analyze the presence of the loop space of the oil production system linked to objects and actions on the Rio Grande do Norte territory. From the so-called "oil shock", an event that caused global developments in several countries, Petróleo Brasileiro S/A (PETROBRAS) increased investments in drilling geological basins in Brazil. In the year 1973 was drilled in the sea area well which led to commercial production of oil and gas in Rio Grande do Norte. From that point on were added in some parts of the Potiguar territory, large systems of coupled objects to actions caused by several agents. In this context, geographic situations have been reorganized due to an unprecedented space circuit production accompanied by a new circle of cooperation. In the state happen all instances of the circuit: the production, distribution and consumption. In light of the theory of the geographical area seek to direct our thoughts to the operation of these bodies, and they are linked to material and immaterial flows multiscales. This perspective allows us to think the territory of Rio Grande do Norte entered into a new territorial division of labor characterized by specialization regional production. Oil activity was implemented in the territory of Rio Grande do Norte at a time marked by productive restructuring of various economic sectors. The oil sector has been acting increasingly linked the scientific and informational, with a view to increasing productivity. The presence of this circuit demanded the territory, specifically the Mossoró, an organizational structure that is different from the vast system nationally integrated private commercial corporations to small corporations, all of them relating directly or indirectly to PETROBRAS. The flows between companies whose headquarters are located in distant states and even countries have generated a continuous movement of goods, people, information and ideas, which is also causing new materialities in the territory